Motherland : growing up with the Holocaust - Goldberg, Rita 1949- (Halban, 2014)
Like Anne Frank, Hilde Jacobsthal was born in Germany and brought up in Amsterdam. Unlike Anne Frank, she survived the war and Otto Frank later became her godfather.--Back cover.